The Significance of Repetition in the Thirtieth Part of the Holy Quran: the Thirtieth Part of the Holy Quran - Salim Saputra (Rumah Riset Publisher, 2023)
This research is to reveal the meaning of repetition linguistically and idiomatically. Likewise, to teach the types of repetition, its purposes, its ruling, and its application in the thirtieth part of the Holy Qur’an, and its impact on linguistic study. This research is a library research with the aim of researching the thirtieth part of the Holy Quran. This research focuses on patterns of recurrence. Data analysis utilized content analysis techniques with the method of observation for data sources who wish to explore the question of recurrence pattern. The results of the research show (1) that the repetition in the thirtieth part of the Holy Qur’an is to warn the unbelievers and the believers, about removal and the resurrection, about the reward in the Hereafter as people did in this world. (2) The meaning of the word is human beings, those who believed, taught good deeds, advised each other to truth, and advised each other to patience, meaning: the first is Abu Jahl, the second is Abu Bakr, the third is Umar, the fourth is Uthman, and the fourth is Ali. May God be pleased with the four caliphs, and curse Abu Jahl.